A comparison of blood stream infections with extended spectrum beta-lactamase-producing and non-producing Klebsiella pneumoniae in pediatric patients - Sevgen Tanır Basaranoglu; Yasemin Ozsurekci; Kubra Aykac; Eda Karadag Oncel; Asiye Bıcakcigil; Banu Sancak; Ali Bulent Cengiz; Ates Kara; Mehmet Ceyhan (BMC, 2017)
Abstract Background Rapid development and global spread of multidrug resistant Klebsiella pneumonia (K. pneumoniae) as a major cause of nosocomial infections is really remarkable. The aim of this study was to explore risk factors for health care associated blood stream infections (BSI) caused by ESBL-producing K. pneumoniae in children and analyze clinical outcomes. Methods A retrospective review of patients younger than 18 years-old with blood stream infection caused by K. pneumoniae was performed. Patients with ESBL-producing K. pneumoniae isolates were compared with ESBL-non-producing isolates in terms of risk factors, outcome and mortality. Results Among 111 K. pneumoniae isolates 62% (n = 69) were ESBL -producing K. pneumoniae. The median total length of hospitalization and median length of stay in hospital before infection was significantly higher in patients with ESBL-producing isolates than ESBL-non-producing. Use of combined antimicrobial treatment was significantly different between ESBL-producing and ESBL-non-producing groups, 75.4% and 24.6%, respectively (p = 0.001). Previous aminoglycoside use was higher in cases with ESBL -producing isolates (p = 0.001). Logistic regression analysis showed a significant correlation between mortality and use of combined antibiotics (OR 4.22; p = 0.01). Conclusion ESBL production in K. pneumoniae isolates has a significant impact on clinical course of BSIs. Total length of hospitalization, length of hospital stay before infection, prior combined antibiotic use and use of aminoglycosides were significant risk factors for development of ESBL-producing K. pneumoniae related BSI.